Challenges in combating crimes against humanity - Timofieieva, Liliia (Vilnius University Open Series, 2023)
On February 24, 2022 Russian Federation started a full-scale invasion of Ukraine. It was shooting at dwellings, kindergartens, orphanages and ambulances by Russian invaders. As a result, a huge number of Ukrainians have already been killed. Damages have been caused to the Ukrainian economy, property and culture as well.The best way to deal with crimes against humanity and war crimes as well is the integration and unity of the international community in combating these crimes. Information technologies can be used both to commit criminal offenses, including those related to terrorism and war propaganda, and to combat crime. In particular, the relevant instruments to combat crimes were developed by European legislation. Moreover, it is proposed to provide additional guarantees for the implementation of decisions of international institutions against the aggressor state, to improve the mechanism for imposing sanctions on a state that has violated international agreements.Finally the human rights standards should comply with people who have committed and been involved in crimes against humanity. The civilized world should respond and ensure security with civilized methods.